MENJEMBATANI WAHYU DAN AKAL: PARADIGMA PEMIKIRAN BUYA HAMKA DALAM REALITAS PENDIDIKAN AL-AZHAR INDONESIA - William Jasson Ngangi; Sa’adi; Muhammad Aji Nugroho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article analyzes the thought of Buya Hamka (1908–1981) in the context of contemporary Islamic education in Indonesia, highlighting its relevance to the educational system implemented in Al-Azhar Indonesia schools. The study employs a conceptual–philosophical approach using a critical hermeneutic–interpretative method to examine Buya Hamka’s major works through textual, intertextual, and contextual analysis. The findings demonstrate the importance of integrating faith, knowledge, and morality as the foundation of an integral educational model oriented toward the formation of the whole person (insan kamil) within the educational system of Al-Azhar Indonesia schools. This paradigm is grounded in a humanistic–transcendental concept, emphasizing a balance between the development of human potential and God-consciousness. The implementation of these values is evident in Al-Azhar Indonesia schools through a centralized curriculum package developed by the Al-Azhar Indonesia Foundation, the cultivation of religious practices, and character formation based on the exemplary conduct of teachers or ustadz. This article contributes to the strengthening of a philosophy of Islamic education that is contextually responsive to the realities of the Muslim community and Indonesian society, adaptive to the challenges of education in the global era, and centered on spirituality as the core of students’ character formation.